Three new low-osmolality contrast agents: a comparative study of patient discomfort. - Smith, D C; Yahiku, P Y; Maloney, M D; Hart, K L (American Journal of Neuroradiology, 1988)
Relative patient discomfort resulting from carotid injections of three new low-osmolality contrast agents was assessed in 78 patients. Omnipaque-300 (iohexol), Isovue-300 (iopamidol), and hexabrix (ioxaglate) were sequentially injected into both common carotid arteries of each patient. Patients were asked to rank the relative intensities of the three injections on each side. Mean patient rankings revealed that Hexabrix was preferred most often, Omnipaque-300 next, and Isovue-300 the least. The differences are statistically significant. We conclude that while patients usually tolerated all intracarotid low-osmolality contrast agents rather well, the agent preferred most often was Hexabrix.